Tinjauan Sanitasi Kolam Renang Tirta Srinadi Klungkung Tahun 2021 - Ida Ayu Putri Windari; Nyoman Purna (Poltekkes Kemenkes Denpasar, 2021)
Ida Ayu Putri Windari1, Nyoman Purna2 Abstract : Tirta Srinadi swimming pool opened on April 13th 2012, located at Banjar Minggir, Gelgel, Klungkung Regency and it has two swimming pools. Preliminary observations showed the swimming pools for toddlers and children, there are floating objects on the water, smell of chlorine scent is too stinging, the floor around the pool is slippery, poorly maintained, no urinal and hand washing in the swimming pool area. This research is conducted to find out the swimming pool sanitation condition which includes the water quality, sanitation facility, and construction of the building. The result is divided into two categories; sanitary condition does not qualify if the score is 0-30,5 and 30,6-61 is qualified. The results showed that Tirta Srinadi Swimming Pool fulfilled the requirements because from 61 items examined; 48 points